FDI on economics growth; Indonesia case study - Haris, Samsul; Danila, Nevi (MEC-J (Management and Economics Journal), 2018)
FDI is one of the factors that encourage the growth of the economy, especially for developing countries. Indonesia has prepared an economic policy package and a taxation policy for booting the investments, including FDI. This paper investigates whether the FDI is one of the essential instruments to improve the growth of Indonesia economy. Multiple regression with GDP as a dependent variable; and FDI, Trade, Government Expenditure, and Inflation as independent variables are employed. The data is from 1985 up to 2015 period. FDI does not have any impact on GDP, while others variables influence the growth of the economy. It suggests that the goals of FDI, namely technology transfer, development of human resources, are not achieved entirely. It implies that the package of economic policy and taxation are not enough for FDI to have the impact on GDP, but others factors, such as wage rate, labor skills, transport and infrastructure, and property rights, must be developed.Â